1998
DOI: 10.1021/ja982131u
|View full text |Cite
|
Sign up to set email alerts
|

Excited States of the Phthalimide Chromophore and Their Exciton Couplings:  A Tool for Stereochemical Assignments

Abstract: The electronically excited states of the phthalimide chromophore have been studied by means of linear dichroism (LD) of samples partially oriented in poly(vinyl alcohol) films, magnetic circular dichroism (MCD), and circular dichroism (CD) spectroscopy. On the basis of the LD measurements, the low-energy tail (340−320 nm) of the first absorption band is assigned to an out-of-plane polarized n→π* transition (I). At higher energy, the electronic spectrum is resolved into contributions from five π→π* transitions:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
54
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 37 publications
6
54
0
Order By: Relevance
“…Monoimides, like phtalimides and 1,8-naphtalimides, have been used successfully in crystal engineering [8] and as chromophores in stereochemical studies [9][10][11]. Most recently, it has been demonstrated that bichromophore consisting of the benzoate substituted in the ortho position with the naphthalimide group (the NAB chromophore) has the ability to act as a sensor of chirality of aliphatic secondary alcohols [12].…”
Section: Introductionmentioning
confidence: 99%
“…Monoimides, like phtalimides and 1,8-naphtalimides, have been used successfully in crystal engineering [8] and as chromophores in stereochemical studies [9][10][11]. Most recently, it has been demonstrated that bichromophore consisting of the benzoate substituted in the ortho position with the naphthalimide group (the NAB chromophore) has the ability to act as a sensor of chirality of aliphatic secondary alcohols [12].…”
Section: Introductionmentioning
confidence: 99%
“…These include use as acceptors for rigid electron-transfer model systems, [1][2][3][4] as linkers in electron donor-acceptor molecules, [5][6][7] as constituents of threading intercalators for DNA, 8 molecules stabilizing oligonucleotide bulged duplex, 9 rigid molecular clefts, 10 macrocyclic receptor molecules, 11 electrically conducting dendrimers, 12 as well as UV absorbing agents in polymers. 13 Recently, we reported the study of electronic states and exciton coupling of aromatic monoimides phthalimides 14,15 and 1,8-naphthalimides. 16 These imides are considered stereochemical probes for nonchromophoric amino groups and have been used successfully for the determination of absolute configuration 14,15,17 and conformation 18 of chiral amines.…”
mentioning
confidence: 99%
“…13 Recently, we reported the study of electronic states and exciton coupling of aromatic monoimides phthalimides 14,15 and 1,8-naphthalimides. 16 These imides are considered stereochemical probes for nonchromophoric amino groups and have been used successfully for the determination of absolute configuration 14,15,17 and conformation 18 of chiral amines.…”
mentioning
confidence: 99%
“…Our numerical results demonstrate how much less efficient may the NDEC mechanism be with respect to the DEC mechanism on similar chromophores. Of course, several successful applications of nondegenerate exciton chirality are known . However, the combination of NDEC and twisted chromophores, or chromophores with possibly large second sphere chirality, as in the case of quassinoids and chlorahololides, is very likely to produce ECD effects surmounting those due to exciton coupling.…”
Section: Resultsmentioning
confidence: 99%